Coastal processes with engineering applications - Dean, Robert G. 1930-2015 (Cambridge University Press, 2002)
The world's coastlines, dividing land from sea, are geological environments that are unique in their composition and the physical processes affecting them. At the dynamically active intersection of land and the oceans, humans have been building structures throughout history. Initially used for naval and commercial purposes, more recently recreation and tourism have increased activity in the coastal zone dramatically. Shoreline development is now causing a significant conflict with natural coastal processes. This text on coastal engineering will help the reader understand these coastal processes and develop strategies to cope effectively with shoreline erosion. The book is organized in four parts: (1) an overview of coastal engineering, using case studies to illustrate problems; (2) hydrodynamics of the coastal zone, reviewing storm surges, water waves, and low frequency motions within the nearshore and surf zone; (3) coastal responses including equilibrium beach profiles and sediment transport; (4) applications such as erosion mitigation, beach nourishment, coastal armoring, tidal inlets, and shoreline management.